Key-exposure resilient integrity auditing scheme with encrypted data deduplication - Xiangsong ZHANG; Chen LI; Zhenhua LIU (Tongxin xuebao)
For the problems of key-exposure,encrypted data duplication and integrity auditing in cloud data storage,a public auditing scheme was proposed to support key update and encrypted data deduplication.Utilizing Bloom filters,the proposed scheme could achieve client-side deduplication,and guaranteed that the key exposure in one time period didn’t effect the users’ private key in other time periods.The proposed scheme could solve the conflict between key-exposure resilient and encrypted data deduplication in public auditing scheme for the first time.Security analysis indicates that the proposed scheme is strong key-exposure resilient,confidentiality,detectability,and unforgeability of authentication tags and tokens under the computation Diffie-Hellman hardness assumption in the random oracle model.